2020
DOI: 10.3390/nu12092705
|View full text |Cite
|
Sign up to set email alerts
|

Household Engagement in Both Aquaculture and Horticulture Is Associated with Higher Diet Quality than Either Alone

Abstract: The consumption of high-quality diverse diets is crucial for optimal growth, health, and wellbeing. Objective: This study assessed the diet quality of households by their type of engagement in homestead aquaculture and/or horticulture. Socio-demographic determinants of diet quality were also studied. Method: Diet quality was assessed using a nutrient adequacy ratio (NAR), based on the preceding 7 days’ dietary recall at the household level. Adult male equivalent units (AMEs) were used for age- and sex-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The mean adequacy ratio (MAR) was calculated as an overall measure of diet quality [ 26 ], using the nutrient adequacy ratio (NAR), in accordance with previous studies [ 33 , 34 , 35 ]. The NAR for a given nutrient is the ratio of an individual’s intake to the age- and sex-specific EAR [ 26 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…The mean adequacy ratio (MAR) was calculated as an overall measure of diet quality [ 26 ], using the nutrient adequacy ratio (NAR), in accordance with previous studies [ 33 , 34 , 35 ]. The NAR for a given nutrient is the ratio of an individual’s intake to the age- and sex-specific EAR [ 26 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies focusing on other interventions not included in the review provide encouraging evidence to link aquaculture to nutrition outcomes. Nutrition‐sensitive fish production interventions may have the potential to improve diet quality (Ahern et al, 2020 ; Akter et al, 2020 ) by increasing the consumption of own‐produced and highly nutritious fish and improving the households' diversity of diets, particularly when the programmes include polyculture systems producing small indigenous fish species (Baten et al, 2018 ; Castine et al, 2017 ; Roos et al, 2007 ). More generally, this literature suggests that the adoption of nutrition‐sensitive aquaculture (i.e., prosustainability policies specifically focused on equal access to nutritious food), could provide a strong framework to allow for increases in nutrition (Gephart et al, 2021 ), particularly in low‐income settings (Thilsted et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Examples include growing rice, fish and crustaceans in the same plot, concurrently or in rotation; growing climbing vegetables on frames built over ponds; and planting fruit trees or coconuts on pond banks 18 . Recent research has found that household engagement in aquaculture and horticulture simultaneously is associated with higher diet quality than either alone 19 . However, to date, little attention has been paid to whether IAA practices enhance production of micronutrients by smallholder farmers 20 .…”
Section: Mainmentioning
confidence: 99%